Aujuhu al-Tasyabuhi wa al-Tanahuri Baina al-Lughataini al-Arabiyah wa al-Tamiliyah Ala Mustawa al-Ashwat - Mohammed Cassim Sithy Shathifa (Departement of Arabic Language and Literature, IAIN Syekh Nurjati Cirebon, 2020)
Language is every sound the people use to express their ideas and communicate with others. It is the basis of any language. Every language has its own unique systems in phonemic and orthographical symbols. According to this concept, Arabic is a Semitic language whereas Tamil is Indo –European language, there is no doubt that it is difficult to foreign language learners to identify the place of articulation of the unfamiliar sounds, its pronunciations and writing format. Among them are the Tamil – speaking Muslims who use and learn Arabic as a foreign language. They face difficulties in pronouncing and writing Arabic letters, proper nouns and term words due to the lack of clarity in the sounds between these two languages. This study try to identify similarities and differences between the sound of Arabic and Tamil languages. This research focus on descriptive and contrastive methods to analyze the data gathered from secondary data such as books and previous studies related to the topic. The result indicates that the Arabic letters are differ from Tamil letters in terms of their number, writing method and their shapes. And also, it has six vowels similar to the six vowels of Tamil language in pronunciation. But they differ in places of articulation and its aspects. Thus, Consonants of Arabic differ from Tamil consonants in pronunciation places of articulation and IPA for them. Consequently, this study will support to determine the pronunciation of Arabic letters and read Arabic language in the best way.إن اللغة هي أصوات يعبر بها كل قوم عن آرائهم وأفكارهم، وهي أداة تساعد على الاتصال بالآخرين. وكل لغة تتركب من جوانب أربعة : الأصوات، الصرف، النحو ، المعنى. وأما الأصوات فهي أساس اللغة، ولكل لغة نظام صوتي خاص ورموز اصطلاحية. من خلال هذا النظر إلى إن اللغة العربية من العائلة اللغوية السامية والتاملية من مجموعة اللغات الهندو - أوروبية، ومما لاشك فيه يصعب على متعلمي اللغة الأجنبية تحديد مخارج الأصوات الجديدة ونطقها وكتابتها. ومنهم المسلمون الناطقون باللغة التاملية الذين يستخدمون ويتعلمون اللغة العربية كلغة أجنبية، فهم يواجهون المشقة في نطق وكتابة الحروف والأعلام والمصطلحات العربية لعدم الوضوح في أصوات اللغتين العربية والتاملية. فتركزت هذه الدراسة تحديد أصوات اللغتين العربية والتاملية، والكشف عن مواقع الشبه والخلاف الصوتي بين اللغتين. استخدمت هذه الدراسة المنهج الوصفي والتقابلي لتحليل المعلومات الثانوية التي حصلت عليها من الدراسات السابقة والكتب والمجلات والمقالات وماتتعلق بهذا الموضوع من الشبكات الإلكترونية. وفي ختام هذه الدراسة قد حددت الباحثة نتائج شتى، ومنها: إن الحروف العربية تتناحر عن الحروف التاملية من حيث عددها وطريقة كتابتها واختلاف أشكالها حسب المواقع في الكلمات. كما أن في اللغة العربية ستة أصوات صائتة وهي تتشابه ستة أصوات صائتة في اللغة التاملية حسب النطق ولكن هناك تناحرا بين صوائتهما من حيث المخرج والصفة، كما أن الصوامت العربية تتناحر كثيرا عن الصوامت التاملية من حيث النطق والمخارج والرموز الصوتية الدولية لها. وإن هذه الدراسة تساعد على المسلمين وغير المسلمين الناطقين باللغة التاملية في تحديد نطق الأصوات العربية وقراءة اللغة العربية بأحسن وجه في المستقبل بواسطة الوضوح بين أصوات هتين اللغتين.